Thrombolysis With Plasmin: Implications for Stroke Treatment - Marder, Victor J.; Jahan, Reza; Gruber, Theresa; Goyal, Abha; Arora, Vik (Stroke (1970), 2010)
Plasmin is a direct-acting thrombolytic agent with a striking hemostatic safety advantage over plasminogen activators in animal models of thrombolysis and bleeding. In contradistinction to plasminogen activators, which risk bleeding at any effective thrombolytic dose, plasmin is tolerated without bleeding at several-fold higher amounts than those needed for thrombolysis. Plasmin has been safe in a current trial in patients with peripheral arterial or graft occlusion, and efforts are now directed toward therapy of stroke caused by cerebral artery occlusion. A rabbit (4 kg body weight) model of 2-hour, thrombin-induced middle cerebral artery occlusion using angiographic documentation of vascular patency and recanalization was used to perform a dose-ranging study of plasmin, delivered by catheter over a median duration of 10 minutes. Plasmin induced early recanalization in all animals (3 per group) within 10 minutes after discontinuation of 3, 2, or 1 mg of agent infusion. Control saline infusion failed to induce recanalization in 3 of 3 subjects. Plasmin rapidly induces middle cerebral artery recanalization, as determined in an angiogram-based animal model of arterial occlusion. Based on these data and other information, a phase I/IIa clinical trial of plasmin in human middle cerebral artery ischemic stroke has been initiated.